2019
DOI: 10.3389/fchem.2019.00495
|View full text |Cite
|
Sign up to set email alerts
|

Advance of Nano-Composite Electrospun Fibers in Periodontal Regeneration

Abstract: Periodontitis is considered to be the main cause of tooth loss, which affects about 15% of the adult population around the world. Scaling and root-planning are the conventional treatments utilized to remove the contaminated tissue and bacteria, but eventually lead to the formation of a poor connection—long junctional epithelium. Therefore, regenerative therapies, such as guided tissue/bone regeneration (GTR/GBR) for periodontal regeneration have been attempted. GTR membranes, acting as scaffolds, create three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 108 publications
2
65
0
Order By: Relevance
“…Previous works indicated that the use of guided membranes without osteoinductive molecules was generally ineffective for highly mineralized bone regeneration, and thus, osteoinductive molecules have been combined with them. 56,57 Despite many promising results, inflammatory responses often occur during surgery, which results in insufficient mineralization and delayed tissue regeneration. 58 As demonstrated on previous studies, lactoferrin may be a candidate with dual functions for the enhancement of in vivo bone regeneration and suppression of inflammation reactions, however, they have never been studied as an immobilized platform.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works indicated that the use of guided membranes without osteoinductive molecules was generally ineffective for highly mineralized bone regeneration, and thus, osteoinductive molecules have been combined with them. 56,57 Despite many promising results, inflammatory responses often occur during surgery, which results in insufficient mineralization and delayed tissue regeneration. 58 As demonstrated on previous studies, lactoferrin may be a candidate with dual functions for the enhancement of in vivo bone regeneration and suppression of inflammation reactions, however, they have never been studied as an immobilized platform.…”
Section: Discussionmentioning
confidence: 99%
“…1 C). 43 Solution electrospinning fibers are inorganized nanofibers with smaller pores, while melt electrospinning fibers are organized microfibers with larger pores. 40 …”
Section: New Tissue Engineering Technologiesmentioning
confidence: 99%
“…For example, the PLGA 75:25 (75% LA and 25% GA) demonstrated more amorphous structures, a lower hydrophilicity, and slower degradation than PLGA 50:50 [ 116 , 117 ]. As a result of the higher hydrophilicity of the amorphous PLGA copolymer with a higher ratio of PGA (e.g., PLGA 50:50), more water absorption is possible which results in faster hydrolytic degradation rates [ 116 , 118 ]. Therefore, the hydrolysis rates may be dependent on different ratios of LA/GA during fabrication, and the copolymerization process could be used to manufacture optimal drug delivery systems with degradation kinetics [ 119 , 120 ].…”
Section: Synthetic Biopolymers For Periodontal Hard Tissue Regenermentioning
confidence: 99%
“…Rather than 3D scaffolding architectures for bone regeneration, the PLGA biopolymer has been mainly considered and utilized to create nano-/micro-particles to deliver biologics such as growth factors, proteins, drugs, or cells to target tissues [ 78 , 111 , 122 , 123 , 124 , 125 , 126 ]. Moreover, PLGA-based, resorbable barrier membranes have been manufactured for guided bone regeneration (GBR) techniques, which prevent soft tissue infiltration and induce bone formation in defect sites in periodontal tissue engineering [ 118 , 127 , 128 , 129 , 130 ].…”
Section: Synthetic Biopolymers For Periodontal Hard Tissue Regenermentioning
confidence: 99%